SIÇANLARDA DENEYSEL BAKIR UYGULAMASININ OKSİDAN VE ANTİOKSİDAN SİSTEMLER ÜZERİNE ETKİLERİ - TOPLAN, Semlin; DARIYERLİ, Nuran and ÖZÇELİK, Derviş and AKYOLCU, M. Can (Cerrahpaşa Medical Journal, 2014)
Background.- Even though copper is necessary trace element for the organism, some recent studies report that copper may have some oxidative damage effects. Oxidative damage of copper has been reported in recent studies even though it is necessary for organism as a trace element. Present study has been planned to determine the oxidative effects of copper on blood and the defense system. Design.- In this study Wistar albino type female rats weighting 200-250g were used. The control (n=9) and experimental groups (n=9) were fed normal diet and water, the experimental group also received copper in their drinking water for nine weeks. After experimental period serum copper concentrations, erythrocyte superoxide dismutase (SOD) activity and glutathione (GSH) levels and plasma malondialdehyde (MDA) concentrations were measured in both group. Results.- MDA concentrations and SOD activities of experimental group were found higher than controls (p<0.05) and GSH concentration in experimental group was found to be lower than control group animals (p<0.05). Conclusion.- The results of this study may show that copper may lead to increase in lipid peroxidation and SOD activity and GSH levels may also be decreased by effect of copper in blood.